BEHAVIOURAL ARCHITECTURE STUDY ON THE DESIGN OF SOCIAL REHABILITATION CENTER FOR THE BLIND AT SURAKARTA - Nadia Permatasari; Maya Andria Nirawati (Universitas Sebelas Maret Surakarta, 2018)
Social rehabilitation center for the blind in Surakarta is a learning centre for people who is visually impaired, specifically the totally blinded. This facility provides professional activities program in order to regaining and increasing the skills of people with vision impairment, both individuals, families, and group, to carry out their social function fairly, and to live in harmony with the dignity; for instance, social skill learning, provision of additional skills and knowledge, psychosocial and health rehabilitation services, as well as basic daily activities training in Surakarta. The goal of this research is to create a physical space as a place of rehabilitation and counselling for the blind to live independently by providing a safe, easy, and convenient infrastructure facilities. To meet the goal, the principles of behavioral architecture design will be applied on the concept of the building. Field observation on the blinds’ behavior is used as the research method, to analyze what the blind needed so the facility can accommodate them.